The effect of aerosol size distribution and concentration on the removal efficiency of an acoustic aerosol removal system. (February 2017) - Yuen, W.T.; Fu, S.C.; Chao, Christopher Y.H.
Abstract: Noninvasive aerosol removal processes are sought after in manufacturing industries that utilize powder product recovery. Traditionally, cyclone separators are commonly deployed, however, this method is energy intensive; space demanding and inefficient for particles with a diameter less than 5 μm. While acoustically induced aerosols depositions was proposed as an alternative aerosol removal method which addressed such limitations, the underlying parameters determining the performance of such technique are yet to be explored. This study examines those underlying parameters determining the efficiency of acoustic aerosol removal, such as; the removal efficiencies, varying aerosol inputs, particle initial concentrations and size distributions. Experimental results showed that given the same initial particle number concentrations, aerosols containing two particles sizes, larger (seed) and smaller (test) particles, improved the removal efficiencies for the test particles. A higher seed to test particle concentration ratio further enhanced this effect. For particle number concentrations ranging above 2.0×10 4 #/cm 3, the increase in concentrations enhanced the removal efficiency of aerosols. Further analysis conducted by numerical simulations demonstrated that the deposition of particles depended on their sizes and their initial positions in the acoustic field. A new parameter, deposition cell ratio was proposed to quantify the deposition probability for particles at a given size and in a given domain. Results suggested that the deposition probability of a group of aerosols may be a function of the sum of the probabilities of each individual particle. Highlights: Noninvasive aerosol removal processes are sought for in powder product recovery. Acoustically induced aerosols depositions were proposed as an alternative to the traditional cyclone separator technique. We examined the ability for aerosol removal on different aerosol input, categorized by the particle initial concentrations and size distributions. Both experimental and simulated studies were performed and a non-dimensional parameter, deposition cell ratio was established as the underlying parameter which governed deposition for different size aerosols.